A review on synthesis, properties and biomedical applications of akermanite - Nur Hasnidah Ahmad Shukeri; Syed Nuzul Fadzli Syed Adam; Hasmaliza Mohamad; Heah, Cheng Yong (Penerbit Universiti Kebangsaan Malaysia, 2025)
Akermanite is a bioactive calcium silicate ceramic that recently has drawn large attention and interest in biomedical devices by numerous researchers due to its favorable properties and characteristics because of the prominent element contents in this material which are Ca 2+ , Mg 2+ , and Si 4+ . The properties of akermanite have been studied through size particle, phase analysis, structure morphology, spectra analysis, and thermal analysis. Besides, the mechanical strength and biological properties of the akermanite also has been investigated in order to control the intended properties complied with the proper reactions of the living organism in the human body. However, despite the huge interest in akermanite in biomedical applications, a very restricted knowledge on the akermanite overview regarding its behavior and potentials are hardly to be acquired to the best of our abilities. Therefore, this review is to highlight and discuss the properties of akermanite formed upon the various methods of synthesis and various processing parameters applied and its feasible potentials in a broad range of biomedical devices practices.